The Use of English Attack Strategies in EFL Class - Mahmoud, Asmaa’ Sirry (Technium Social Sciences Journal, 2022)
English Attack is an English Language learning resource designed for today's digital generation of EFL/ESL learners. It combines exercises on short-format video clips from the latest movies hit,T>V series, documentaries, and music videos, learning games, and social networking functionalities-all within a motivational personalized coaching ecosystem. English Attack is an appropriate for all levels of English language learners, and complementing class-based and teacher-led English language instruction. English Attack aims to revolutionize English language learning by leveraging the power of online entertainment. Learning units consistvof exercises based on authentic,current short-format entertainment content.